2001
DOI: 10.1016/s0022-5347(05)65810-7
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Varicocele: Tauber Antegrade Sclerotherapy Versus Palomo Repair

Abstract: These data suggest that the failure rate was similar in both groups. The principal advantages of sclerotherapy are simplicity, decreased cost and lack of hydrocele formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 22 publications
2
23
0
Order By: Relevance
“…The retrograde technique may be associated with migration of embolization coils, thrombophlebitis, arterial puncture, hydroceles and a high unperformable rate of up to 30% with recurrence in 3-11% [13][14][15][16]. The antegrade technique can also be performed under local anaesthesia with a much shorter operative time, lower unperformable rate and low incidence of recurrence or persistence [17][18][19][20]. The complication rate is only 3-8%, but testicular artery injury may occur in up to 1% of cases [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The retrograde technique may be associated with migration of embolization coils, thrombophlebitis, arterial puncture, hydroceles and a high unperformable rate of up to 30% with recurrence in 3-11% [13][14][15][16]. The antegrade technique can also be performed under local anaesthesia with a much shorter operative time, lower unperformable rate and low incidence of recurrence or persistence [17][18][19][20]. The complication rate is only 3-8%, but testicular artery injury may occur in up to 1% of cases [20].…”
Section: Discussionmentioning
confidence: 99%
“…Both techniques involve radiographic exposure which may be deleterious to an already subfertile patient. In conclusion, since these two low-cost techniques can be performed under local anaesthesia in a day-care setting, they are probably more suitable for recurrent varicoceles since this would avoid difficult exposure in a previously operated field and allow precise delineation of the vascular channels prior to their occlusion [17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…The failure rate can be as high as 20% in some series. Mazzoni et al [7] reported the best results in adolescents, which were a failure rate of 4% and no hydroceles. The high failure rate associated with this technique does not make up for the cost savings that the Europeans commonly tout in there reports because they rarely include the cost of the retreatments in their calculations.…”
Section: Introductionmentioning
confidence: 98%
“…Sclerotherapy has become a popular option in Europe, but has gained few advocates in the United States [5][6][7]. The failure rate can be as high as 20% in some series.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, only 3 groups have reported their experience in this particular category of patients. [9][10][11] The antegrade scrotal approach is very simple and rapid. In all series, the mean operating time was shorter than 30 minutes.…”
Section: Discussionmentioning
confidence: 99%